2011
DOI: 10.1371/journal.pone.0026898
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Subepithelial Myofibroblasts Support in vitro and in vivo Growth of Human Small Intestinal Epithelium

Abstract: The intestinal crypt-niche interaction is thought to be essential to the function, maintenance, and proliferation of progenitor stem cells found at the bases of intestinal crypts. These stem cells are constantly renewing the intestinal epithelium by sending differentiated cells from the base of the crypts of Lieberkühn to the villus tips where they slough off into the intestinal lumen. The intestinal niche consists of various cell types, extracellular matrix, and growth factors and surrounds the intestinal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
170
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(176 citation statements)
references
References 18 publications
4
170
1
1
Order By: Relevance
“…Our implantation scheme relies on co-culture with myofibroblasts. This limitation is not unique to the collagen system; we have observed that both murine (unpublished results) and human 7 crypts grown in Matrigel require myofibroblasts for successful subcutaneous in vivo engraftment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our implantation scheme relies on co-culture with myofibroblasts. This limitation is not unique to the collagen system; we have observed that both murine (unpublished results) and human 7 crypts grown in Matrigel require myofibroblasts for successful subcutaneous in vivo engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…7 The ISEMF were cultured using myofibroblast medium consisting of DMEM/Low Glucose/ GlutaMAX (Invitrogen), 10% FBS (Invitrogen), 1 · Antibiotic-Antimycotic (Invitrogen), 0.25 U/mL insulin (Sigma), 20 ng/mL recombinant murine EGF (PeproTech, Rocky Hill, NJ), and 10 mg/mL transferrin (Sigma).…”
Section: Intestinal Subepithelial Myofibroblast Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Within the intestinal stem cell niche, signals to maintain the undifferentiated nature of these cells, and thereby the epithelial integrity, are provided by surrounding mesenchymal cells. The alpha-smooth muscle actin expressing intestinal subepithelial myofibroblasts (ISEMFs) are known to support long-term epithelial growth in vitro and wound healing, for instance (Lahar et al, 2011;Seltana et al, 2010). This effect may be caused by factors such as R-Spondin-2, a Wnt-agonist, but it is still unclear if cell-cell contacts are necessary (Lei et al, 2014).…”
Section: Co-culture and Pathophysiological Modelsmentioning
confidence: 99%
“…However, depletion of Paneth cells or knockout of Wnt3 in the epithelial cells of the intestine did not show an obvious in vivo phenotype (Durand et al, 2012;Farin et al, 2012), indicating that other functionally important Wnts are made by epithelial or stromal niche cells. Several groups have demonstrated that stromal cells can support the growth of intestinal epithelium in culture (Farin et al, 2012;Lahar et al, 2011). Intestinal stromal cells express multiple Wnts (Farin et al, 2012;Gregorieff et al, 2005 One approach to address the functionally relevant source of Wnts in the small intestine is to globally target their secretion.…”
Section: Introductionmentioning
confidence: 99%